Etika Berinternet (Netiket) untuk Meningkatkan Literasi Digital Pelajar di SMAN 2 Banjarmasin: Internet Ethics (Netiquette) to Improve Student Digital Literacy at SMAN 2 Banjarmasin - Inayatul Ulya Ahyati; Huda Sya’rawi; Linda Permanasari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Internet ethics (netiquette) is one indicator of digital ethical competence in digital literacy. Schools are one of the targets of the digital literacy program promoted by the government, although they have participated in the digital literacy program, not all schools in Banjarmasin understand what is meant by internet ethics. SMAN 2 Banjarmasin (SMADA) is a partner in this program, which is also one of the schools whose students have never received socialization/material about internet ethics. Based on that problems, this community service program is carried out by socializing internet ethics to improve students' digital literacy at SMADA. At the end of the socialization session, students will have evaluation about internet ethics. This session was held to find out the extent of their understanding about netiquette. Based on evaluation results, SMADA’s students understand the material that has been delivered. Students are able to assess whether or not they have implemented internet etiquette. This internet ethics socialization made students understand the importance of applying internet ethics. They understand what to upload or not when using social media and other digital tools.